Management of skeletal Class III malocclusion with face mask therapy and comprehensive orthodontic treatment - Kirthika Muthukumar; N M Vijaykumar; M C Sainath (Wolters Kluwer Medknow Publications, 2016)
Orthopedic correction of skeletal Class III malocclusion in a growing patient is crucial as it can circumvent future surgical procedures. Further, as surgery is done only at a later stage, early treatment helps to avoid the detrimental effects produced by the facial disfigurement on the patient's social life. This case report describes the treatment of a child aged 9 years 6 months who had a skeletal Class III malocclusion. The treatment plan involved the use of a reverse pull headgear (facemask) and multibracket appliance therapy resulting in successful correction of the malocclusion. The treatment results were highly satisfactory resulting in improved facial esthetics, a skeletal Class I with a Dental Class I molar and canine relationship, an ideal overjet and overbite. Thus, dentoalveolar camouflage, if done in properly selected cases, alleviates the need for surgical intervention. The patient is being monitored until the end of growth to ensure the stability of treatment results.